NIÑOS, NUEVAS TECNOLOGÍAS Y GÉNERO: HACIA LA DEFINICIÓN DE UNA AGENDA DE INVESTIGACIÓN - Dra. Carolina Duek,Dr. Sebastián Benítez Larghi,Dra. Marina Moguillansky, (Fonseca, Journal of Communication, 2023)
The relationship between information and communications technology (ICT) and a number of aspects of contemporary everyday life constitutes a productive field inside cultural studies. The constant enquiries about uses, socialization and representations place ICT in the midst of Social Sciences research in the 21st century. This article aims to compose a research agenda for future research on ICT related to gender, children and play. All those axes have been independently analyzed, but the intersections and articulations we found in our research open new perspectives to question.